Bugsy - Levinson, Barry; Toback, James; Johnson, Mark Steven, 1964-; Beatty, Warren, 1937-; Bening, Annette; Keitel, Harvey; Kingsley, Ben, 1943-; Mantegna, Joe.; Morricone, Ennio; Tri-Star Pictures; Columbia TriStar Home Video (Firm); Mulholland Productions; et al. (Burbank, CA : ColumbiaTriStar Home Video, 1998)
Benjamin "Bugsy" Siegel was a ruthless mobster who had it all, and then met a woman who wanted more. Their love affair was passionate, tempestuous and ultimately tragic
Closed captioned for the hearing impaired
Videodisc release of the 1991 motion picture
Special features include: Theatrical trailers, scene selections
Music, Ennio Morricone
Warren Beatty, Annette Bening, Harvey Keitel, Ben Kingsley, Joe Mantegna
DVD format; Dolby digital, stereo, widescreen version, fullscreen version
Keywords: Siegel, Bugsy, -- 1906-1947. -- Drama; Gangsters -- Drama; Feature films -- United States; Gangster films; Films for the hearing impaired; Drama; Video recordings